An Analysis of Bound Morphemes In Firehouseâ€™s Song Lyrics Entitled "When I Look Into Your Eyes" - Sukmono Bayu Adhi (Syntax Literate, 2022)
This study aims to analyze the bound morphemes in the lyrics of the song â€œWhen I Look into Your Eyesâ€. It is a descriptive qualitative study where data analysis is presented in tabular form. Based on the result of the study, it can be concluded that the song lyrics contain 9 bound morphemes which two of them are derivational morphemes that function as class changing affixes. They each change an adjective to a verb, and a verb to a noun. The other seven data are inflectional morphemes which function as plural, past-tense, past participle, and third-person singular. From the calculation results, it is seen that the number of derivational morphemes is 22.5 percent while inflectional morphemes reach 77.5 percent. so it can be concluded that the inflectional morphemes are the most dominant.